Gender portrayals revisited: searching for explicit and implicit stereotypes in Cypriot magazine advertisements - Tsichla, Eirini; Zotos, Yorgos (My University, 2016)
The study pursues a line of inquiry into contemporary gender stereotypes drawn from print advertisements in Cyprus. The investigation of implicit modes of stereotyping suggested by Goffman across explicit gender roles yield novel and interesting insights that broaden existing knowledge on male and female advertising depictions. Through a content analysis of 3.729 characters, the study reveals the existence of gender cliches in Cypriot magazine advertisements. Neither male nor female evolving roles are adequately reflected in advertisements, as men tend to be portrayed in traditional masculine stereotypes while women lean towards decorative portrayals. Implicit stereotyping is more likely to suggest the subordination and lower status of women compared to men. The study indicates that advertising in Cyprus reinforces the diffusion of hostile sexism by the underrepresentation of professional women and their commonplace portrayal in body revealing attires. At the same time, the high proportion of women's implicit subordination signifies benevolent sexism. The distorted representation of both genders raises key public policy concerns, as diminishing portrayals hold sway upon men's and women's psychological well-being and professional development.
Keywords: Gender stereotypes; Gender roles; Sexism; Content analysis; Print advertisements